Indigenous Cultural-Heritage Resource Management System: Designing an Open-Source Based Technical Framework - Dutta, Anirban; Mukhopadhyay, Parthasarathi (Journal of Information and Knowledge, 2022)
This paper reports the development of a digital indigenous or aboriginal cultural heritage archive prototype to understand more specifically how to manage cultural heritage resources for local needs, for traditional and indigenous communities, and in libraries, archives, and museums as they seek to manage, preserve, strengthen, develop, and reuse these resources. The tribes who are the earliest inhabitants of India are economically and socially the least advanced, as they live in isolated and self-contained groups, and are distinct culturally and ethnically from mainstream societies. Historically, colonization, ignorance of mainstream societies, etc., have dominated thousands of indigenous cultures that have ceased to exist or have been marginalized to the brink of extinction. This exploratory study is an attempt to find the tools and techniques that can assist in building an information system for indigenous culture. It considers the need for integration of such a system with a library retrieval system, and the prototype includes the indigenous cultural resources of the Rabha tribe of North-East India to illustrate the idea and suggest a prototype based on open source software and open standards.